Bhakta kavi Bammera Potanāmātya kī kavitā mādhurī - Pāṇḍuraṅgārāva, Āi., 1930- (Haidarābāda : Antara Rāshṭrīya Telugu Saṃsthāna, 1982)
Study of Pōtana, 15th century Telugu poet.
Cover title: Madhura kavi Potanā.
Hindi and Telugu (Devanagari)
Mode of access: Internet.
Keywords: Pōtana, -- 15th cent. -- Criticism and interpretation